2014
DOI: 10.3319/tao.2014.06.11.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Viral Shunt in Nitrogen Cycling in Synechococcus Spp. Growth in Subtropical Western Pacific Coastal Waters

Abstract: Viruses play an important role in aquatic environments in bacteria and phytoplankton mortality and also in carbon and nutrient recycling through the lysis of living cells. However, the effects of nitrogen regenerated by viral lysis on the growth of picophytoplankton are rarely studied. This study investigated whether the presence of viruses has a positive effect on the daytime frequency of cell division in Synechococcus spp. in the coastal waters of the western subtropical Pacific Ocean. Using cell incubation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In our previous study, we observed that viruses significantly affect the nutrient regeneration, and enhanced the growth rates in Synechococcus during the daytime in the subtropical western Pacific coastal waters [27]. Data from the previous studies indicated that viral-induced ammonium regeneration resulted in increased growth of Synechococcus [28,29]. The abovementioned results could explain the meager increase in the growth rates of Synechococcus in the nutrient-enriched bottles in this study.…”
Section: Discussionsupporting
confidence: 67%
“…In our previous study, we observed that viruses significantly affect the nutrient regeneration, and enhanced the growth rates in Synechococcus during the daytime in the subtropical western Pacific coastal waters [27]. Data from the previous studies indicated that viral-induced ammonium regeneration resulted in increased growth of Synechococcus [28,29]. The abovementioned results could explain the meager increase in the growth rates of Synechococcus in the nutrient-enriched bottles in this study.…”
Section: Discussionsupporting
confidence: 67%
“…may depend on locally recycled nutrients and a similar study found that viral-induced ammonium regeneration resulted in an increased growth as well as the proportion of dividing Synechococcus spp. cells in the warmer seasons [33]. The above results could explain why Synechococcus spp.…”
Section: Seasonal Dynamics Of Synechococcus Spp and Picoeukaryotic Ab...mentioning
confidence: 79%
“…displayed higher proportion of dividing Synechococcus spp. cells (FDC) in virus existing treatment than that in the virus-reduced treatment (37% vs. 5%) (Tsai et al 2014).…”
Section: Resultsmentioning
confidence: 96%